(untitled) (Journal of University of Babylon for Engineering Sciences, 2025)
Urban intersection is essential to the effectiveness of road networks, particularly in regions that are close to important services like government buildings, schools, and hospitals. A crucial intersection with frequent traffic jams and operational inefficiencies is the Al-Warda signalized intersection, which is situated in the center of Samawah city. The intersection still operates at an inadequate Level of Service (LOS F) even with fixed-time traffic lights, indicating the urgent need for action. This study fills this gap by using a simulation-based methodology to assess and enhance the Al-Warda intersection’s performance. Two well-known traffic simulation programs are used in the study: VISSIM, which simulates traffic in great detail at the microscopic level, and Synchro 8, which does deterministic analysis based on the Highway Capacity Manual (HCM). Using video footage taken during peak hours throughout a week, the case study focuses on real-world settings. In order to create precise simulation models, geometric features, traffic volumes, and signal timings were retrieved and processed. After the model was calibrated and validated, a number of augmentation techniques were attempted, such as geometric redesign (lane widening and re-marking) and signal timing optimization. The outcomes demonstrated a notable enhancement in intersection performance. The LOS improved from F to C, and the average delay decreased from 111.1 seconds to 36.7 seconds, demonstrating a significant operational improvement. The results show how well geometric adjustments and simulation-based traffic signal optimization work together to reduce congestion at city intersections. Future studies should investigate AI-driven traffic management techniques and signal control to improve urban mobility even more.